2011
DOI: 10.2119/molmed.2011.00123
|View full text |Cite
|
Sign up to set email alerts
|

Human Skeletal Muscle Stem Cell Antiinflammatory Activity Ameliorates Clinical Outcome in Amyotrophic Lateral Sclerosis Models

Abstract: Mesenchymal stem cell (MSC) therapy is considered one of the most promising approaches for treating different neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS). We previously characterized a subpopulation of human skeletal muscle-derived stem cells (SkmSCs) with MSC-like characteristics that differentiate into the neurogenic lineage in vitro. In the present study, we evaluated the SkmSC therapeutic effects in the most characterized model of spontaneous motor neuron degeneration, the Wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…“Human skeletal muscle-derived stem cells (SkmSCs)” showed a positive effect, after implantation in the brain lateral ventricles of wobbler mice. Like HuCB-MNCs, transplanted SkmSCs did not reach the ventral horns of cervical spinal cords, but magnetic resonance imaging (MRI) showed that some clusters of cells migrated in the spinal parenchyma and the signal was maintained up to 18 weeks after transplantation (Canzi et al 2012). The evidence of a marked expression of specific human anti-inflammatory cytokines in the brain of transplanted wobbler mice seems to confirm the hypothesis that a bystander effect of soluble factors, released by SkmSCs, even far from the affected areas, might play a neuroprotective role.…”
Section: Towards the Treatment Of Alsmentioning
confidence: 99%
“…“Human skeletal muscle-derived stem cells (SkmSCs)” showed a positive effect, after implantation in the brain lateral ventricles of wobbler mice. Like HuCB-MNCs, transplanted SkmSCs did not reach the ventral horns of cervical spinal cords, but magnetic resonance imaging (MRI) showed that some clusters of cells migrated in the spinal parenchyma and the signal was maintained up to 18 weeks after transplantation (Canzi et al 2012). The evidence of a marked expression of specific human anti-inflammatory cytokines in the brain of transplanted wobbler mice seems to confirm the hypothesis that a bystander effect of soluble factors, released by SkmSCs, even far from the affected areas, might play a neuroprotective role.…”
Section: Towards the Treatment Of Alsmentioning
confidence: 99%
“…The therapeutic efficacy of SkmSCs (subpopulation of human skeletal muscle-derived stem cells) with MSC-like features was evaluated after intracerebroventricular injection to the Wr mouse (Wobbler mouse, the most typical model of spontaneous motor neuron degeneration) by Canzi et al (2012). The research team confirmed that MRI can visualize stem cells and follow their migration after transplantation in the CNS of rodents (Canzi et al, 2012).…”
Section: Application Of Iron Oxide Nanoparticles In the Treatment Of Alsmentioning
confidence: 93%
“…Finally, the multifaceted mechanisms and variety of cell types proposed to contribute to ALS pathogenesis support cellular therapy development using non-neuronal progenitors. Intracerebroventricular injection of skeletal muscle stem cells induces anti-inflammatory cytokine production, improved motor function, and protection of neuromuscular junctions in wobbler mice [57]. Intraspinal transplantation of glialrestricted progenitor cells into the cervical spinal cord of G93A-SOD1 rats, as a means to increase astrocyte numbers in spinal cord regions controlling critical respiratory function, attenuates motor neuron loss, slows respiratory functional declines, and improves survival by approximately 17 days [58].…”
Section: Progenitor Cellsmentioning
confidence: 99%
“…Upon clinical translation, however, more sophisticated techniques to identify and follow the fate of grafted cells will be required. For instance, the labeling of cells with superparamagnetic iron oxide nanoparticles or reporter genes allows cell graft tracking using advanced imaging technologies [28,57,[90][91][92][93][94][95]. Notably, these approaches can provide insight into the migratory potential of grafted cells following systemic or targeted injections, as demonstrated in both a large animal and human trials [73,86].…”
Section: The Future Of Stem Cell Therapies For Alsmentioning
confidence: 99%